MODEL OF GRIPPER OF ROBOT MANIPULATOR WHEN OVERLOADING PLANT MICROSHOOTS FROM THE TRANSPORT CONTAINER TO THE WORKING CONTAINER (ҚазҰУ Хабаршысы. Математика, механика, информатика сериясы, 2023)
In this article, a model is proposed for determining the parameters of the structural elements of a novel pincer robot for transporting plant microsprouts from a transport container in vitro to a working container with soil at the stage of their adaptation in soil during microclonal propagation.Scientific and practical result of the research is the creation of an innovative robotic complex of a manipulation device with a phalanx gripper for the transfer of plant microsprouts from a transport container in vitro to a working container with soil at the stage of their adaptation in soil during microclonal propagation, and the testing of its physical prototype in the adaptation of 3000 pieces of woody microsprouts. Plants with roots in the soil. The obtained research results will affect the scientific and technical potential and competitiveness of scientists in the Republic of Kazakhstan. In the Republic of Kazakhstan there are no studies on automation of the technology of microclonal propagation of plants for their mass production, the application of which would allow obtaining a large number of plants and reducing the cost of planting materials. Besides, the practical results of research on an innovative robotic complex will reduce the import of planting material of woody plants from other countries for the design of settlements in the Republic of Kazakhstan.In this regard, the need for native, high-quality planting material for woody plants will increase. One of the main solutions to the problem of landscaping in the settlement areas of the Republic of Kazakhstan is to obtain native high-quality planting material for woody plants by microclonal propagation.